ҚАРАҚАЛПАҚСТАН ҚАЗАҚЛАРЫ ТИЛИНДЕГИ МИНЕЗ-ҚУЛЫҚ МӘНИСИН БИЛДИРЕТУҒЫН СОМАТИЗМ ФРАЗЕОЛОГИЗМЛЕР - Бекниязов, Б. (SCIENCE and SOCIETY, 2020)
The article highlights the peculiarities of dialectical somatic phraseologies that characterize human behavior in the Kazakh language which is used in Karakalpakstan. Dialectical somatic phrases based on the anatomical body names are compared in the Kazakh and Karakalpak literary languages.